Coronaviruses and Central Nervous System Manifestations - Khateb, Mohamed; Bosak, Noam; Muqary, Maryam (Frontiers in Neurology, 2020)
SARS-CoV-2 is a highly pathogenic coronavirus that has caused an ongoing worldwide pandemic. Emerging in Wuhan, China in December 2019, the virus has spread rapidly around the world. Corona virus disease 2019 (COVID-19), which is caused by SARS-CoV-2, has resulted in significant morbidity and mortality. The most prominent symptoms of SARS-CoV-2 infection are respiratory. However, accumulating evidence highlights involvement of the central nervous system (CNS). This includes headache, anosmia, meningoencephalitis, acute ischemic stroke, and several presumably post/para-infectious syndromes and altered mental status not explained by respiratory etiologies. Interestingly, previous studies in animal models emphasized the neurotropism of coronaviruses; thus, these CNS manifestations of COVID-19 are not surprising. This minireview scans the literature regarding the involvement of the CNS in coronavirus infections in general, and in regard to the recent SARS-CoV-2, specifically.